Edith Stein: formação, atuação e mediação cultural - análise das Conferências de 1926 a 1933 - Pedrosa, Rarden Luis Reis (2025)
The interwar period (1918-1939) was marked by armed conflicts and significant technological advancements. Notably, Germany emerged as a terrain of contrasts and deep reflections during this period, the context in which Edith Stein lived. Stein was born in Breslau in 1891 and was killed in the Auschwitz-Birkenau Concentration Camp in 1942. The ongoing research focuses on the development of Stein’s educational thought from a historical perspective, considering the period between 1926 (the phase of her first conference) and 1933, when she converted to Catholicism. Fifteen conferences delivered in Germany have been selected, based on a comparison with her formative journey and academic work, to understand her influence in the public sphere. The main objective is to investigate her academic formation, political-social role as a woman, and the process between Judaism and Catholicism experienced by Stein, considering her intellectual heritage and her connections to the historical context. These events, particularly her conversion to Catholicism, were decisive for her work and intellectual production. For historical investigation and to explore the connections of her intellectual network with the turbulent interwar period, particularly in Germany, this study adopts the analytical categories of cultural mediation, networks and places, as well as intellectual sociability. These are approached from the perspective of Intellectual History and the History of Intellectuals, which provide essential insights into understanding ideas and actions, their disputes, appropriations, circumstances, and power relations